Production potential of short duration rice (Oryza sativa) in relation to age of seedlings, date of transplanting and crop geometry - KAUR, PRABHJIT; SAINI, K S; KAUR, KIRANDEEP; KAUR, JASHANJOT (The Indian Journal of Agricultural Sciences, 2023)
An experiment was conducted at the research farm of Punjab Agricultural University, Ludhiana, Punjab during 2018 and 2019 to determine the production potential of rice (Oryza sativa L.) in relation to age of seedlings, date of transplanting and crop geometry. The results revealed that growth and productivity of short duration rice crop were improved by transplanting younger seedlings of 3 and 4 weeks age (nursery sown on June 12 and June 19) as compared to the older ones 5 and 6 week old seedlings (nursery sown on May 29 and June 5). Transplanting of rice at 25th June and 10th July with 20 cm × 15 cm crop geometry recorded better growth, yield attributes and higher yield as compared to 15 cm × 15 cm crop geometry. Rice transplanted on 10th July required fewer irrigations (14 and 17) as compared to the crop transplanted on June 25 (16, 19) in 2018 and 2019, respectively. This led to a water saving of 12.5 and 10.5% during those respective years, without compromising the yield. It is worth noting that a single irrigation was applied at a depth of 7.5 cm. For higher saving in irrigation water, nursery of PR 126 can be sown up to June 20 and 25–30 days old seedlings can be transplanted up to July 10 at 20 cm ×15 cm spacing.